PENGARUH KOMPETENSI PEDAGOGIK DOSEN TERHADAP AKTIVITAS BELAJAR MAHASISWA PERGURUAN TINGGI AGAMA ISLAM (PTAI) KABUPATEN INDRAGIRI HULU - Afrida Yanis (STAI Nurul Falah Airmolek, 2019)
In higher education, lecturers are spearheading the success of students. The ability of faculty to manage and implement the teaching learning process is essential in order to improve students' learning activities. To enhance the learning activities of students,faculty required to increase pedagogical competence. The background of this research because there are some students' creativity was still lacking and half the value is below standard. This research was carried out since the beginning of August until the month of November 2016 is housed in the College of Islamic Religion (STAI Nurulfalah Airmolek and STAI Madinatun Najah Rengat). The subjects were students STAI Nurulfalah Airmolek and STAI Madinatun Najah Rengat. While the object of research is a Lecturer Pedagogic Competence Influence of Student Learning Activity Against Islamic Religion (PTAI) Indragiri Hulu. Collecting data in this study using questionnaires and documentation. Data were analyzed by descriptive quantitative research with percentages. To analyze the effect of Competence Pedagogical Lecturer Student Learning Activity Against Islamic Religion (PTAI) Indragiri Hulu collected data were analyzed using a quantitative approach with Pearson Product Moment Correlation technique. By (PPM) =Based on data analysis, it can be seen from some of the test results that have been the author of the analysis, based on the correlation of test results obtained 0.988 with 0.000 significance. The significance value 0.000 <0.05, then Ho is rejected, it means Ha accepted, meaning that the Significant Influence of Competence Pedagogical Lecturer Student Learning Activity Against Islamic Religion (PTAI) Indragiri Hulu.